A Large Manganese‐doped Polyoxotitanate Nanocluster: Ti14MnO14(OH)2(OEt)28. Issue 7 (22nd May 2013) - Chen, Yang; Sokolow, Jesse; Trzop, Elzbieta; Chen, Yu‐Sheng; Coppens, Philip
Abstract A large manganese‐doped polyoxotitanate nanocluster, Ti14MnO14(OH)2(OEt)28, has been synthesized under solvothermal conditions. Its structure is similar to previously reported Ti17O24(OiPr)20, but lacks 5‐fold coordinated Ti atoms which are potential binding sites for photosensitizer molecules. The Mn atom is located at the center of the Keggin structure with Ti‐O bond length indicative of Mn2+, a conclusion confirmed by NEXAFS measurements. Solid‐state band gap measurements of the complex show a significant decrease compared with undoped polyoxotitanate nanoclusters and anatase, indicating the potential of Mn‐doping for visible light photocatalysis.